2011
DOI: 10.1016/j.ijfatigue.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the role of non-metallic inclusions on the anisotropic fatigue behaviour of forged steel

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. AbstractForged components are known to show high cyclic and monotonic mechanical properties. This is mainly due to a better compactness and a finer microstructure introduced by the forming process. However, this good mechanical behaviour is sometimes a source of anisotropy especially when the microstructural heterogeneities are not randomly distributed and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…However, it has been observed that for other metallic materials the parameters m 1 and m 2 can vary significantly. For example, for the hot rolled steel, MetascoMC (25MnCrSiVB6), there is more scatter associated with the fatigue strength of the material without defects than when defects are present (m 1 = 30 and, m 2 = 48) [14,15,16].…”
Section: The Parameters M 1 M 2 or Mmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has been observed that for other metallic materials the parameters m 1 and m 2 can vary significantly. For example, for the hot rolled steel, MetascoMC (25MnCrSiVB6), there is more scatter associated with the fatigue strength of the material without defects than when defects are present (m 1 = 30 and, m 2 = 48) [14,15,16].…”
Section: The Parameters M 1 M 2 or Mmentioning
confidence: 99%
“…This work is only briefly described below as it has been well documented elsewhere. [12,13,14,15,16].As such, the objective of this section is to highlight the usefulness and flexibility of the proposed modelling framework.…”
Section: Application To Other Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The inclusions found from the fracture surfaces were vastly different especially in the aspect ratio -in parallel the inclusions were mostly regular oxides and also failures from the matrix occurred whereas, in the other direction, aspect ratios were shown to be in the range of 5-30, being mostly oxides, oxide clusters and sulfides. The manganese sulfides are known for their ability to deform and thus emphasize the anisotropy created in such deformation [26]. Makino highlighted that, for such elongated inclusions, the √ area overestimates the maximum stress intensity factor.…”
Section: Forming Effectsmentioning
confidence: 99%